PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN MATERI HAK ANAK DI RUMAH DAN DI SEKOLAH - Purwanto Purwanto (Jurnal Pembelajaran Prospektif, 2022)
At the end of the Civics lesson (PKN) on children's rights at home and at school, an evaluation was held. The results showed that the obtained data from 5 students of 27 grade 1 students in the second semester of SDN 7 Sungai Mata-Mata Simpang Hilir District, North Kayong Regency whose scores were below 65 or 19.34 % have not reached the minimal passing grade (KBM), which is 65, and the average score of the class is still low, at 80.66. Based on the identification of the problem, the students did not pay attention to the teacher's explanation of "The rights of children at home and at school". The research purpose of learning improvement is to increase students' understanding of their rights at home and at school by using pictorial media. By using pictorial media during the second cycle of the research, the observation results of the formative tests showed good and satisfactory results, with a total of 22 students who had scored 70 and above.